温庭筠小说集《乾馔子》研究 = Study on Wen Tingyun's short story collection : Gan Zhuan Zi - 洪媛 Hong, Yuan (2018)
几经修改润饰，这篇毕业论文终于如期完成。在此，我想向帮助和支持我的 人表达忠心的感谢。 首先我要感谢我的论文指导老师曲景毅助理教授。在整个写作过程中他给予 我耐心与鼓励，并细心地提出修改建议，让我不断地学习和进步，对古典文学有 了更深入的了解。 其次，我想感谢研究生三年间所有教授过我的老师们，是你们的悉心教导， 让我积累足够的知识来完成这篇论文。 我也要感谢我的父母这段时间对我的关心和督促，在我失落和彷徨时给予的 陪伴。 This thesis focuses on Wen Tingyun’s short story collection ‘Gan Zhuan Zi’, and attempts to examine the literary value of this short story collection. Gan Zhuan Zi is incomplete and what remains of this collection are 33 pieces of short stories found in Tai Ping Guang Ji. It is, however, a pity that only 17 of them contain relatively complete plots and focused characterization. As the original collection is long lost, there are very few records and critiques of ‘Gan Zhuan Zi’ in history. The thesis comprises six sections. The introduction provides a brief description of the short story collection and the development of Tang Dynasty phantastic short stories. It also offers an overview of relevant literature reviews and the significance of this research topic. Chapter one traces the general narrative of Gan Zhuan Zi so as to arrive at the estimated time of writing of these short stories. Chapter Two explores the motivations behind Wen Tingyun’s writings. He could have been using his short stories to express his feelings and his interest in the entertainment value of short stories or to record the lives of the masses. He could also have wanted to exchange ideas with other literary scholars and perfect his talent for all literary forms. Chapter Three compares the similarities and differences between Wen Tingyun's short stories, and his poetry and prose. It also provides an overview of the literary style of his complete oeuvre.The forth chapter compares two late Tang short story collections: Gan Zhuan Zi and Youyang Zazu. In terms of content and writing style, Youyang Zazu failed to escape from old concept and still followed earlier traditions. While Wen Tingyun had broken the ideas and concepts of former dynasties, adopts anti-traditional models, anti-formularized ideas, as well as typical plot settings. For the influence on the later generations, only a few single articles from Gan Zhuan Zi had more obvious influences, while the complete collection Youyang Zazu made a significant influence to Liao Zhai Zhi Yi (Strange Stories from a Chinese Studio) in Qing Dynasty. This chapter also analyzes on development of short story context from ‘Sou Shen Ji’ to ‘Gan Zhuan Zi’ and ‘Youyang Zazu’ to ‘Liao Zhai Zhi Yi’, re-evaluating the value on collection of the late Tang dynasty short stories, Gan Zhuan Zi and Youyang Zazu, and conclude they had played an important part of the short story history. Finally, the last chapter discusses reasons on neglecting of Wen Tingjun's short stories. The original book is a single book, it is easy to distinct by spreading in the form of copying, and he was well known by his Ci-poetry and poetry, former researchers have neglected his prominent talent on short story writing. Moreover, the characteristics of his short stories and obscuration caused by the inequality of different literary form also affected the evaluation of his works.